BLENDED LEARNING FOR SPEAKING ABILITY: STUDENTS’ MOTIVATION IN EFL CLASSROOM - Citra Prasiska Puspita Tohamba; Wa Ode Hesran; Abdul Halim (LP2M Institut Agama Islam Muhammadiyah Sinjai, 2022)
The purpose of this study is to explore whether blended learning might encourage students in the English-speaking second-grade class at SMPN 9 Kendari. This study is designed precisely to identify these issues. The focus of the research in this study is a second grade Junior High School class of 36 students. A qualitative research design was used for this study. Data is gathered through classroom observation and documentation. The findings show that blended learning is unsuccessfully implemented to encourage students' motivation in speaking class because there is an imbalance in the results between online and offline learning. The study also exposes the difficulties that students experience when studying online, such as their inability to use smartphone mobile functions, poor internet connections, and a lack of engagement as well as the teachers' insufficient supervision of such learning to prevent students from concentrating on the learning process.